2001: tricentenaire de la Grande Paix de Montréal - Beaudoin, Léo (Montréal en tête, 2001)
issued: 2001-24-00
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Le tricentenaire de la Grande Paix de Montréal. Louis-Hector de Callière (1646-1703), artisan de la Grande Paix - Beaudoin, Léo (Montréal en tête, 2001)
issued: 2001-23-00
Keywords: Callière; Louis-Hector de; Gouverneurs; Grande Paix de Montréal

Le tricentenaire de la Grande Paix de Montréal. Montréal, juillet-août 1701 - Beaudoin, Léo (Montréal en tête, 2001)
issued: 2001-21-00
Keywords: Autochtones; Callière; Louis-Hector de; Fortifications; Fourrure; Gouverneurs; Grande Paix de Montréal; Guerre

Le renouveau de la géopolitique au temps des mégalopoles en réseau et son applicabilité à un atlas de Montréal - Marsolais, Alain (Université du Québec à Montréal, 2001)

1920-2001, 81 ans de solidarité ouvrière - Fournier, Roseline; Houle, Louis-Serge (Conseil central du Montréal métropolitain, CSN, 2001)
Keywords: Confédération des syndicats nationaux; Conseil central des syndicats nationaux de Montréal

Le nationalisme anglo-québécois à travers "The Gazette" et le "Montreal Daily Star" pendant la Seconde Guerre mondiale - Lacasse, Chantal (Université de Montréal, 2001)
Keywords: Montreal Gazette; Montreal Star; Nationalisme

Les âges de Montréal - Linteau, Paul-André (Forces, 2001)
Number: 131

La gestion de la demande des déplacements: un examen des possibilités et des contraintes dans le cas des étudiants de l'Université de Montréal - Sévigny, Éric (Université de Montréal, 2001)
Keywords: Université de Montréal; Étudiants

La réorganisation du travail à la raffinerie Shell de Montréal-Est, de 1989 à 1999 - Delorme, Marie-Josée (Université de Montréal, 2001)
Keywords: Montréal-Est; Pétrole; Travail

The Great Peace of Montreal of 1701: French-Native Diplomacy in the Seventeenth Century - Havard, Gilles (McGill-Queen's University Press, 2001)
Translators: _:n12897
Keywords: Autochtones; Français; Grande Paix de Montréal

From the Ghetto to the Main: the Story of the Jews of Montreal - King, Joe (Montreal Jewish Publications Society, 2001)
Keywords: Juifs

Le Saint-Laurent et la structuration de l’espace montréalais, XVIIe-XXe siècle - Robert, Jean-Claude (Études canadiennes / Canadian Studies, 2001)
Number: 50

Montréal, 1701: Planting the Tree of Peace - Havard, Gilles (Recherches amérindiennes au Québec et Musée McCord, 2001)
Translators: _:n60062
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Montréal, 1701: planter l'arbre de paix - Havard, Gilles (Recherches amérindiennes au Québec et Musée McCord, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

La Grande Paix: chronique d'une saga diplomatique - Beaulieu, Alain; Viau, Roland (Libre Expression et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

Le transport à vélo: le cas des étudiants de l'Université du Québec à Montréal - Moran, Anne-Marie (Université du Québec à Montréal, 2001)
Keywords: Cyclisme; Université du Québec à Montréal; Étudiants

Pectus est quod disertos facit: éloquence et sublime dans la Rhétorique (1796) de Jacques-Antoine Houdet - Bélanger, Anne; Landry, Alexandre (Archives et fabrique du textile littéraire, 2001)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

Le développement économique communautaire dans un contexte métropolitain: le cas de Montréal - Silvestro, Marco (Département d’études urbaines et touristiques de l'Université du Québec à Montréal, 2001)

Joseph de Nancrède et la presse française d’Amérique au temps de la Gazette de Montréal (1780-1800) - Andrès, Bernard (Les Cahiers des Dix, 2001)
Number: 55
Keywords: Français; Montreal Gazette

La Faculté de théologie de l'Université de Montréal: mémoire et histoire, 1967-1997 - Sauvé, Madeleine (Fides, 2001)
Keywords: Théologie; Université de Montréal

Pigeon Hole Parking, (Montréal 1956-2000): mort d’un témoin moderne - Durand, Daniel (Continuité, 2001)
issued: 2001-21-00
Keywords: Automobile; Quartiers; Vieux-Montréal

L’Académie de Montréal (1778): fiction littéraire ou projet utopique - Doyon, Nova (Mens, 2001)
issued: 2001-21-00
Keywords: Gazette Littéraire de Montréal; Mesplet; Fleury

The Great Peace of Montreal, 1701 - Matusky Gedeon, Julia (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Autochtones; Français; Grande Paix de Montréal

Jules Gilbert: pionnier de l'éducation sanitaire - Gaumer, Benoît; Desrosiers, Georges (Lidec, 2001)
Keywords: Médecine; Université de Montréal

Les lieux de la paix de 1701, et autres considérations sur les campements amérindiens à Montréal - Johnson, Laurence (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

La commercialisation des produits de la recherche en génie au Laboratoire d’électronique appliquée de l’École polytechnique de Montréal, 1937-1975 - Auger, Jean-François (Histoire, économie et société, 2001)
Number: 1
Keywords: Ingénieurs; Université de Montréal; École polytechnique

L’archive et l’invention littéraire: le cas des Mystères de Montréal d’Auguste Fortier (1893) - Ducharme, Nathalie (Archives et fabrique du textile littéraire, 2001)

Les chemins de la mémoire. Monuments et sites historiques du Québec. Supplément 1987-1999 - Commission des biens culturels du Québec. (Publications du Québec, 2001)
Keywords: Commémoration; Monuments; Patrimoine

Du Petit Dublin au quartier chinois - Létourneau, Isabelle (Continuité, 2001)
issued: 2001-21-00
Keywords: Chinois; Quartier chinois; Quartiers

La pensée politique de René Lévesque dans ses chroniques au Journal de Montréal et au Jour entre 1970 et 1976 - Lagacé, François (Université de Sherbrooke, 2001)
Keywords: Jour (Le); Journal de Montréal (Le); Lévesque; René

The Great Peace: Chronicle of a Diplomatic Saga - Beaulieu, Alain; Viau, Roland (Libre Expression, 2001)
Translators: _:n12489
Keywords: Autochtones; Français; Grande Paix de Montréal

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Analyse de l'engagement organisationnel de professionnels œuvrant dans une institution universitaire québécoise - Côté, Ghislaine (Université du Québec à Montréal, 2001)
Keywords: Université du Québec à Montréal

Notre-Dame-de-Bonsecours: une chapelle et son quartier - Simpson, Patricia; Pothier, Louise (Fides, 2001)
Keywords: Notre-Dame-de-Bonsecours (chapelle); Quartiers; Vieux-Montréal; Églises

Le tricentenaire de la Grande Paix de Montréal. Août 1701 - Beaudoin, Léo (Histoire Québec, 2001)
Number: 2
Keywords: Autochtones; Callière; Louis-Hector de; Français; Gouverneurs; Grande Paix de Montréal; Guerre; Iroquois

L'Œuvre de l'historienne Louise Dechêne - Dépatie, Sylvie (Montréal en tête, 2001)
issued: 2001-24-00
Keywords: Historiens

Une petite maison... Un grand homme: Hormidas Laporte - Cloutier, Gabrielle (Montréal en tête, 2001)
issued: 2001-21-00
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Le fantasme métropolitain. L'architecture de Ross et Macdonald - Lachapelle, Jacques (Presses de l'Université de Montréal, 2001)
Keywords: Gares; Gratte-ciel; Hôtellerie; Magasins

Histoire des écoles d'Hochelaga-Maisonneuve. Tome 1. L'École Notre-Dame-de-l'Assomption (Louis-Jolliet) - Cadotte, Robert; Noël, Colette (Commission scolaire de Montréal et Atelier d'histoire Hochelaga-Maisonneuve, 2001)
Keywords: Hochelaga (quartier); Maisonneuve; Quartiers

Perceptions linguistiques à Montréal - Laur, Elke (Université de Montréal, 2001)
Keywords: Langue

Le métro de Montréal, 35 ans déjà - Clairoux, Benoît (Hurtubise HMH, 2001)
Keywords: Transport en commun

Memory and Migration: Ethiopian Jews in Montreal - Djerrahian, Gabrielle (Université de Montréal, 2001)
Keywords: Africains; Juifs

Saint-Denis de Montréal: répertoire des mariages, 1899-1994 - Audet, Claire (Société généalogique canadienne-française, 2001)
Keywords: Mariage; Registres

Plus que parfaites: les aides familiales à Montréal, 1850-2000 - Groot, Raphaëlle de; Ouellet, Élizabeth (Remue-ménage, 2001)
Keywords: Domestiques; Femmes; Institut du Bon-Conseil

Le regroupement municipal en marche: Méga-Montréal et Méga-Longueuil - Collin, Jean-Pierre (Québec 2002. Annuaire politique, social, économique et culturel, 2001)

Transmission culturelle aux enfants par de jeunes couples immigrants. Montréal, Québec, Sherbrooke - Helly, Denise; Vatz-Laaroussi, Michèle; Rachedi, Lilyane (Immigration et Métropoles, 2001)
Keywords: Enfants

Entre conjoncture et fusions: l’économie de Montréal dans l’expectative - Manzagol, Claude (Québec 2002. Annuaire politique, social, économique et culturel, 2001)

The Historical Record and Adolescent Girls in Montreal’s Red-Light District - Myers, Tamara (Framing Our Past: Constructing Canadian Women’s History in the Twentieth Century, 2001)
Keywords: Enfants; Femmes; Prostitution

Saint-Thomas-d'Aquin de Montréal: baptêmes et mariages, 1908-1941 - de Lamirande, Cécile (Société généalogique canadienne-française, 2001)
Keywords: Mariage; Registres

Making Public Pasts: the Contested Terrain of Montréal's Public Memories, 1891-1930 - Gordon, Alan (McGill-Queen's University Press, 2001)
Keywords: Anglophones; Francophones; Monuments; Protestants

Jeunes filles affiliées aux gangs de rue à Montréal: cheminements et expériences - Fournier, Michèle (Université de Montréal, 2001)
Keywords: Criminalité; Délinquance

Le mouvement communautaire haïtien de Montréal en tant que mouvement social - Boucard, Alix (Université de Montréal, 2001)
Keywords: Haïtiens

L’architecture des lieux de spectacle à Montréal de 1987 à 2000 - Hervé, Geneviève (Université de Montréal, 2001)

La problématique d'un ensemble conventuel à Montréal: le domaine de Saint-Sulpice - Wertheimer, Ève (Université de Montréal, 2001)
Keywords: Communautés religieuses; Sulpiciens

L'institutionnalisation des corporations de développement économique communautaire sur l'Île de Montréal - Silvestro, Marco (Université de Montréal, 2001)

L'identité ethnolinguistique de jeunes adultes issus de couples mixtes francophones/anglophones à Montréal - Hadiri, Myriam (Université de Montréal, 2001)
Keywords: Anglophones; Francophones; Langue

Le monde social de la rue: expériences des jeunes et pratiques d'intervention à Montréal - Bellot, Céline (Université de Montréal, 2001)
Keywords: Itinérance

Le jeûne du ramadan en contexte de migration: le cas des immigrants d'origine marocaine à Montréal - Grégoire, Anne-Josée (Université de Montréal, 2001)
Keywords: Maghrébins; Marocains

Analyse journalière des déterminants du volume des accidents routiers dans la région métropolitaine de Montréal, 1995-1998 - Blais, Étienne (Université de Montréal, 2001)
Keywords: Routes

Les homicides reliés aux motards sur le territoire de la Communauté urbaine de Montréal de 1994 à 2000 - Gignac, Hélène (Université de Montréal, 2001)
Keywords: Communauté urbaine; Criminalité

Louis-Hector de Callière: Man of War, Man of Peace - Morazain, Jeanne; Cloutier, Ginette; Lelievre, Francine (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2001)
Keywords: Callière; Louis-Hector de; Gouverneurs

Louis-Hector de Callière: homme de guerre, homme de paix - Morazain, Jeanne; Cloutier, Ginette; Lelievre, Francine (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2001)
Keywords: Callière; Louis-Hector de; Gouverneurs

"Identification des valeurs, des objectifs et des finalités actuels et souhaités de l'éducation chez les musulmans de la région de Montréal" - Aoui, Jamel (Université de Montréal, 2001)
Keywords: Musulmans

The Double-Edged Sword: Defining Prostitution in Mainstream Canadian Press - Chapman, Ainsley Claire (Université Concordia, 2001)
Keywords: Montreal Gazette; Prostitution

Segmentation des internautes bancaires montréalais - Mehrez, Karim (Université du Québec à Montréal, 2001)
Keywords: Banques; Internet

Baseball, américanité et culture populaire histoire du baseball à Montréal: 1860-1914 - Coupal, Éric (Université du Québec à Montréal, 2001)
Keywords: Baseball

Pratiques inciviles et sentiment d'insécurité: une étude de cinq parcs montréalais - Léonard, Daniel (Université du Québec à Montréal, 2001)
Keywords: Parcs

Le suicide dans le district judiciaire de Montréal (de 1815 à 1843 et de 1893 à 1903) - Bordeleau, François (Université du Québec à Montréal, 2001)
Keywords: Mortalité

Le discours des acteurs de la crise d'octobre 1970 dans la presse francophone de Montréal (1971-2000) - Leroux, Manon (Université du Québec à Montréal, 2001)
Keywords: Crise d'octobre; Front de Libération du Québec

Parcours d’une collaboration: les intervenants psychiatriques et psychologiques à la Cour des jeunes délinquants de Montréal (1912-1950) - Quevillon, Lucie (Université du Québec à Montréal, 2001)
Keywords: Délinquance; Enfants; Psychologie; Tribunaux

Déterminants de la valeur marchande des propriétés unifamiliales sur l'île de Montréal: évaluation de masse conjuguée aux SIG - Ozdilek, Unsal (Université du Québec à Montréal, 2001)
Keywords: Évaluation foncière

Du képi au kippa: implantation des nouvelles politiques de rapprochement du service de police de la Communauté urbaine de Montréal en milieu hassidique - Shamlian, Isabelle (Université du Québec à Montréal, 2001)
Keywords: Hassidim; Juifs; Police

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal: le cas des Français, des Vietnamiens, des Libanais et des Haïtiens - Ndiaye, Sophie (Université du Québec à Montréal, 2001)
Keywords: Français; Haïtiens; Libanais; Vietnamiens

L'expérience de la pratique de la danse salsa des jeunes adultes dans deux discothèques latines de Montréal: une participation à une culture, une rencontre, un rituel - Burelle, Édith (Université du Québec à Montréal, 2001)
Keywords: Danse; Latino-Américains

Une “vaillante phalange” contre “vieux pontifes”. La réception des Soirées du Château de Ramezay dans le journal Les Débats - Cellard, Karine (Archives et fabrique du textile littéraire, 2001)
Keywords: Ramezay (château de)

L’archive littéraire à la rescousse de l’histoire: le cas des Comédies du Statu quo (1834) - Desjardins, Nancy (Archives et fabrique du textile littéraire, 2001)
Keywords: Archives; Papineau; Louis-Joseph; Rébellions

Ironie, sarcasme et dérision dans Le Canadien (1806-1810) - Laquerre, Marie-Lise; Massé, Stéphanie (Archives et fabrique du textile littéraire, 2001)
Keywords: Humour

Les pratiques de gestion dans les PME de la communauté haïtienne de Montréal - Michel, Dicarmel (École des hautes études commerciales de Montréal, 2001)
Keywords: Haïtiens

La dynamique sociale entourant les jardins communautaires: l'individu, le groupe et le jardin. Le cas de Montréal - Daclon Bouvier, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Groupes populaires; Jardins

Saint-Laurent du village à la ville - Brochu, Johanne; Sokoloff, Béatrice (Ville de Saint-Laurent et Université de Montréal, 2001)
Keywords: Saint-Laurent (ville); Villages

Les bourgeois et leur environnement: la rue Sherbrooke à Montréal en 1901: mémoire de maîtrise d'histoire contemporaine - Pagé, Marine (Université d'Angers (U.E.R. des lettres et des sciences humaines), 2001)
Keywords: Bourgeoisie; Rues; Sherbrooke (rue)

Essai de synthèse ethnohistorique du secteur des Rapides de Lachine. Rapport final - Des Roches, Jacques (Communauté urbaine de Montréal, Service de la mise en valeur du territoire, Division de l'aménagement, 2001)

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Le tourisme culturel à Montréal - Rémillard, Marie-France (Université Laval, 2001)
Keywords: Tourisme

Le grand méridien de Montréal - Bumbaru, Dinu (Continuité, 2001)
issued: 2001-21-00
Keywords: Rues; Saint-Laurent (rue)

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Musique; Noirs

History of landscape architecture in Montreal - Jacobs, Peter; Williams, Ron (Landscape Architecture, 2001)

1883-1889: quand Montréal avait son carnaval! - Dufresne, Sylvie (Cap-aux-Diamants, 2001)
issued: 2001-24-00
Keywords: Carnaval; Patin; Raquetteurs

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Ces médecins montréalais en marge de l'orthodoxie - Desjardins, Rita (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2001)
Number: 2
Keywords: Médecine

La croissance naturelle des Montréalais au XIXe siècle - Olson, Sherry; Thorton, Patricia (Cahiers québécois de démographie, 2001)
Number: 2
Keywords: Mariage; Mortalité

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Montréal, plaque tournante des explorations françaises en Amérique - Conciatori, Christine (Cap-aux-Diamants, 2001)
issued: 2001-22-00
Keywords: Français

Le Parc Jarry de Montréal. 75 ans d'histoire - Hudon, François (Les Éditions Logiques, 2001)
Keywords: Parcs

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
issued: 2001-21-00
Keywords: Noirs; Théâtre

Prévenir l’exurbanisation : le Plan Greber de 1950 pour Montréal - M'Bala, Jose (Urban History Review / Revue d'histoire urbaine, 2001)
Number: 2

Urbanisation et paroisse: le cas de Montréal au XIXe siècle - Robert, Jean-Claude (Atlas historique du Québec : La paroisse, 2001)

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Painting on the Edge: Geometric Abstraction in Montreal, the 1950s - Patterson, Jody (Université Concordia, 2001)
Keywords: Peinture

Plus que parfaites: un siècle de services domestiques à Montréal - Bourbeau, Amélie (Cap-aux-Diamants, 2001)
issued: 2001-22-00
Keywords: Domestiques; Femmes

Exploration d’une ville disparue: Montréal sous le Régime français - Brossard, Jean-Guy (Cap-aux-Diamants, 2001)
issued: 2001-22-00

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Deserting Daughters: Runaways and the Red Light District of Montreal before 1945 - Myers, Tamara (Child Welfare and Social Action: Nineteenth and Twentieth Centuries, 2001)
Keywords: Délinquance

Salsa and its Transnational Moves: The Commodification of Latin Dance in Montreal - Pietrobruno, Sheenagh (Université McGill, 2001)
Keywords: Danse

Le Montréal juif entre les deux guerres / Tsvishn tsvey velt milhomes - Medresh, Israël (Septentrion, 2001)
Translators: _:n32043
Keywords: Juifs

Under Reconstruction: the Family and the Public in Postwar Montréal, 1944-1949 - Fahrni, Magda (Université York, 2001)
Keywords: Famille; Guerre

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

A City Transformed: Manufacturing Districts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Journal of Historical Geography, 2001)
Number: 1
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

That's Not What I Heard: Synchronized Sound Cinema in Montreal 1926-1931 - Stober, JoAnne (Université Concordia, 2001)
Keywords: Cinéma

Groupes, identités et municipalités dans l’histoire de Montréal et de sa région - Linteau, Paul-André (Ministère des Affaires municipales et de la Métropole du Québec, 2001)

La dépression politique des Anglo-Montréalais lors de la crise des années trente - Jedwab, Jack (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Anglophones; Crise

After the Pain, Beauty Remains: Identity and Aesthetics of Body Modification in Montreal - Dermerson, Elizabeth (Université Concordia, 2001)

La renaissance d'un sport organisé au Canada: le hockey à Montréal, 1875-1917 - Vigneault, Michel (Université Laval, 2001)
Keywords: Canadien (Club de hockey); Hockey

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

The Identification of Employment Centres in Canadian Metropolitan Areas: the Example of Montreal, 1996 - Coffey, William J.; Shearmur, Richard (The Canadian Geographer / Le Géographe canadien, 2001)
Number: 3

‘Preach the World’: Canadian Imperialism and Missionary Outreach at the Montreal Diocesan Theological College, 1892-1903 - Mills, Sean (Journal of the Canadian Church Historical Society, 2001)
issued: 2001-21-00
Keywords: Anglicans; Missions; Protestants; Théologie

Entre tradition et modernité. Espaces et temps de loisirs à Montréal et Toronto au XXe siècle - Dagenais, Michèle (Canadian Historical Review, 2001)
Number: 2
Keywords: Mont-Royal (parc); Parcs; Tramways; Transport en commun

Le Front d’action politique (FRAP) à Montréal: de la naissance aux élections (1969-1970) - Comby, Marc (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2001)
Number: 2
Keywords: Groupes populaires; Partis politiques; Élections

La ville, miroir et enjeu de la santé: Paris, Montréal et Alger au XXe siècle - Goubert, Jean-Pierre (Histoire, économie et société, 2001)
issued: 2001-07/2001-09
Keywords: Vaccination; Épidémies

Effect of Premigratory Exposure to Political Violence on the Social Anchorage of Refugees in Montreal - Drapeau, Aline (Université McGill, 2001)

The No.5 Terminal Grain Elevator in the Port of Montreal: Monument in a Shifting Landscape - Senécal, Nathalie H. (Université Concordia, 2001)
Keywords: Patrimoine; Vieux-port

"A Most Detestable Crime": Gender Identities and Sexual Violence in the District of Montreal, 1803-1843 - Ramos, Sandy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Number: 1
Keywords: Femmes

HIV Risk Behaviour and Predictors of Initiation into Prostitution among Female Street Youth in Montreal, Canada - Weber, Amy E. (Université McGill, 2001)

Unmaking Manly Smokes: Church, State, Governance, and the First Anti-Smoking Campaigns in Montreal, 1892-1914 - Rudy, Jarrett (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Number: 1
Keywords: Alcool; Femmes; Prohibition; Tabac; Tempérance

La paroisse urbaine comme communauté sociale: l'exemple de Saint-Pierre-Apôtre de Montréal, 1848-1930 - Ferretti, Lucia (La paroisse, 2001)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

Un projet inconnu de Jacques Gréber: La Cité-jardin de Villeray du Domaine Saint-Sulpice à Montréal - Ploegaerts, Léon (Urban History Review / Revue d'histoire urbaine, 2001)
Number: 2
Keywords: Domaine Saint-Sulpice; Quartiers; Villeray

“Le Québec a charge d’âme”: l’Action française de Montréal et les minorités françaises (1917-1928) - Bock, Michel (Revue d'histoire de l'Amérique française, 2001)
En s'appuyant sur l'exemple de la revue mensuelle L'Action française, cet article cherche à circonscrire la place des minorités françaises du Canada dans le nationalisme canadien-français des années 1920, problématique négligée par les historiens. L'auteur démontre que la conception « romantique » qu'avait la revue de la nation canadienne-française faisait des minorités les vestiges ou le prolongement du grand « Empire français d'Amérique », argument qui sera fréquemment utilisé par la rédaction afin de revendiquer le respect de leurs droits scolaires et religieux. Par ailleurs, ce n'est que lorsque considérés en fonction des minorités françaises que quelques-uns des plus importants thèmes du nationalisme canadien-français, comme la mission providentielle du Canada français, trouvent tout leur sens. La nation étant une entité « organique », L'Action française assignait également au Québec un devoir de solidarité nationale envers les minorités aux prises avec les politiquesassimilatrices de la majorité anglo-protestante du pays.
issued: 2001-24-00
Keywords: Action française (L'); Nationalisme

Dealing with "the Destitute and the Wretched": The Protestant House of Industry and Refuge in Nineteenth-Century Montreal - Harvey, Janice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Number: 1
Keywords: Itinérance; Philanthropie; Protestants

Des rues et des hommes : les commencements des politiques publiques locales en matière de travaux publics à Montréal, 1796-1840 - Fougères, Dany (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2001)
Keywords: Rues; Voirie

Jurys, participation civique et représentation au Québec et au Bas-Canada: les grands jurys du district de Montréal (1764-1832) - Fyson, Donald (Revue d'histoire de l'Amérique française, 2001)
issued: 2001-22-00
Keywords: Criminalité; Juges; Police

Du chemin du Roy à la rue Notre-Dame. Mémoires et destin d'un axe est-ouest à Montréal - Noppen, Luc (Ministère des Transports du Québec, 2001)
Keywords: Routes; Rues

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Les espaces verts de Montréal à la fin du XIXe siècle et au début du XXe siècle: le cas du parc Lafontaine - Héraut, Mariette (Université Michel de Montaigne-Bordeaux 3, 2001)
Keywords: Parc La Fontaine; Parcs

The Practice and Meaning of Bonsai, Ikebana, and Tea in Montreal and Abroad: A Case Study of the Processes of Cultural Globalization - Wilson, Hayley (Université Concordia, 2001)
Keywords: Japonais

L'éducation "idéale" dans un monde "idéal": le Dunham Ladies' College / St. Helen's School et l'élite anglicane du diocèse de Montréal (1870-1930) - Harbec, Marie-Ève (Université McGill, 2001)
Keywords: Anglicans

Les campagnes de sauvegarde de la maison Van Horne et du couvent des Soeurs grises ou les questionnements d'une identité urbaine (Montréal, 1973-1976) - Drouin, Martin (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l’étude de l’architecture au Canada, 2001)
Number: 3-4
Keywords: Communautés religieuses; Couvents; Soeurs Grises; Van Horne (maison); Van Horne; William

L'état de préparation des intervenants de l'Île de Montréal en l'an 2000 face à des pluies diluviennes comme celles du 14 juillet 1987 - Boissonneau, Julie (Université de Sherbrooke, 2001)
Keywords: Climat

Bois urbain et controverses locales, ou comment intégrer la nature à la ville - Sénécal, Gilles; Saint-Laurent, Diane (Québec 2002. Annuaire politique, social, économique et culturel, 2001)
Keywords: Conservation

Verdun, 125 ans d'histoire, 1875-2000 - Gravel, Denis; Lafortune, Hélène (Societe de recherche historique archiv-histo, 2001)
Keywords: Quartiers; Verdun

Le McCord: l'histoire d'un musée universitaire, 1921-1996 - Young, Brian (Hurtubise HMH, 2001)
Translators: _:n11207
Keywords: Musée McCord; Musées

René Lévesque: l'espoir et le chagrin (1976-1980) - Godin, Pierre (Boréal, 2001)
Keywords: Lévesque; René

La FTQ, ses syndicats et la société québécoise - Bélanger, Yves; Comeau, Robert; Métivier, Céline (Comeau & Nadeau, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

La FTQ et le Québec syndical - Clément, Carole; Fédération des travailleurs et travailleuses du Québec (Fédération des travailleurs et travailleuses du Québec, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Analyse comparative des politiques et interventions en habitation - Dansereau, Francine; Divay, Gérard; Rose, Damaris; Sénécal, Gilles; Séguin, Anne-Marie; Aubrée, Loïc (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2001)
Keywords: Logement

Verdun, 125 years of history, 1875-2000 - Gravel, Denis; Lafortune, Hélène (Societe de recherche historique archiv-histo, 2001)
Keywords: Quartiers; Verdun

Analyse comparative des politiques de logement en regard des problématiques et tendances récentes - Dansereau, Francine; Divay, Gérard; Aubrée, Loïc; Rose, Damaris; Sénécal, Gilles; Séguin, Anne-Marie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2001)
Keywords: Logement

15 février 1839: lettres d'un patriote condamné à mort - de Lorimier, François-Marie-Thomas-Chevalier; Nadeau, Jean-François; Desbiens, Marie-Frédérique (Comeau & Nadeau, 2001)
Keywords: Lorimier; Chevalier de; Rébellions

Gustave Francq: figure marquante du syndicalisme et précurseur de la FTQ - Leroux, Éric (VLB, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

La pensée de Gustave Francq, syndicaliste et réformateur social: textes choisis, 1905-1948 - Francq, Gustave; Leroux, Éric (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 2001)

Dupuis Frères: le magasin du peuple: plus d'un siècle de fierté québécoise - Dupuis-Leman, Josette (Stanké, 2001)
Keywords: Commerce de détail; Dupuis Frères; Magasins

La Bibliothèque Saint-Sulpice, 1910-1931 - Lassonde, Jean-René (Bibliothèque nationale du Québec, 2001)
Keywords: Bibliothèque Saint-Sulpice; Communautés religieuses; Sulpiciens

Jacques Parizeau. Tome I - Le Croisé - 1930-1970 - Duchesne, Pierre (Québec Amérique, 2001)

Jean Béliveau: un grand Canadien - Bertrand, Luc (Lidec, 2001)
Keywords: Canadien (Club de hockey); Hockey

Chiniquy - Trudel, Marcel (Lidec, 2001)
Keywords: Chiniquy; Charles

Benjamin Sulte: cet inlassable semeur d'écrits - Marcotte, Hélène (Lidec, 2001)
Keywords: Historiens

Mother Marie-Rose: Eulalie Durocher, 1811-1849 - Laberge, Yolande (Lidec, 2001)
Translators: _:n48594
Keywords: Communautés religieuses; Durocher; Eulalie; Soeurs des Saints Noms de Jésus et de Marie

Norman Hudon 1929-1997. Une vie comme un arc-en-ciel de couleurs - Hudon, François (Lidec, 2001)
Keywords: Caricature; Peinture

René Lévesque and the Parti Québécois in Power - Fraser, Graham (McGill-Queens University Press, 2001)
Keywords: Lévesque; René; Partis politiques

L'île Sainte-Hélène - O'Neil, Jean; Brunet, Pierre Phillipe (Hurtubise HMH, 2001)
Keywords: Île Sainte-Hélène

Répertoire numérique du fonds Rita-Mount - Blain, Hélène (Bibliothèque nationale du Québec, 2001)
Keywords: Peinture

D'audace en mémoire: le lieu dit Lachine, un regard archéologique - Buteau, Hélène; Chevrier, Daniel (Art Gestion, 2001)
Keywords: Lachine; Le Ber; Jacques; Le Moyne de Longueuil; Charles; Maison LeBer-LeMoyne

Jardins d'un autre temps. Deux jardins dans l'esprit de la Nouvelle-France - Tairraz, Monique (Maison Saint-Gabriel et Musée du Château Ramezay, 2001)
Keywords: Alimentation; Jardins; Maison Saint-Gabriel; Ramezay (château de)

Guido Nincheri artiste entrepreneur - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Vitraux; Églises

Guido Nincheri muraliste - Laroche, Ginette; Pellissier, Pierlucio (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Églises

Le vitrail au studio de Guido Nincheri - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Vitraux; Églises

Analyse des valeurs patrimoniales du site et des bâtiments de l'Oratoire Saint-Joseph du Mont-Royal - Tanguay, Caroline (2001)
Keywords: Oratoire Saint-Joseph; Patrimoine

La présentation de la commémoration du 11 novembre dans la presse au Canada et en France: une étude comparative (1919-1999) - Chagnon, Christian (Université de Montréal, 2001)
Keywords: Commémoration; Guerre

The Little Presses that Did: a History of First Statement Press, Contact Press and Delta Canada, and an Assessment of their Contribution to the Rise and Development of Modernist Poetry in Canada during the Middle Part of the Twentieth Century - Tracey, Collett (Université de Montréal, 2001)
Keywords: Poésie; Édition

Discours du patriotisme dans le théâtre québécois du XIXe siècle - Lajoie, Mélanie (Université de Montréal, 2001)
Keywords: Théâtre

Les trajectoires des jeunes d'origine haïtienne dans le système québécois de protection de la jeunesse - Bernard, Léonel (Université de Montréal, 2001)
Keywords: Haïtiens

La production d'art sacré de Charles Daudelin de 1964 à 1992 - Lachance, Valérie (Université de Montréal, 2001)
Keywords: Arts sacrés

La représentation de l'amérindien et de la nature chez Joseph-Charles Taché et Philippe-Joseph Aubert de Gaspé - Tessier, Vicky (Université de Montréal, 2001)
Keywords: Autochtones

La représentation de la Chine dans les médias québécois à l'époque de la Révolution culturelle chinoise (1966-1976) - Desharnais, Daniel (Université de Montréal, 2001)

Appréhender la nation, vivre la diaspora regards arméniens - Lenoir-Achdjian, Annick (Université de Montréal, 2001)
Keywords: Arméniens

Daniel Coussirat (1841-1907): la vie et l’œuvre d’un intellectuel franco-protestant - Hamelin, Charles (Université de Montréal, 2001)
Keywords: Protestants

Libéralisme, nationalisme et catholicisme dans la pensée politique de Claude Ryan au Devoir (1962-1978) - Marcil, Olivier (Université de Montréal, 2001)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan; Claude

Nationalisme et antinationalisme dans le Québec des années 1935-1939 - Bégin, Yves (Université de Montréal, 2001)
Keywords: Nationalisme

Esdras Minville, le catholicisme social et le nationalisme économique, 1923-1939 - Foisy-Geoffroy, Dominique (Université de Montréal, 2001)
Keywords: Minville; Esdras; Nationalisme

Discours critique, discours polémique: littérature et nationalisme dans le journal Les Débats (1900) - Cellard, Karine (Université de Montréal, 2001)
Keywords: Nationalisme

Le théâtre d'intervention et les jeunes de la rue - Dagenais, Bernard (Université du Québec à Montréal, 2001)
Keywords: Itinérance; Théâtre

L'évaluation d'une intervention: le travail de rue dans un organisme communautaire PACT de rue - Allaoui, Saandiya (Université du Québec à Montréal, 2001)
Keywords: Itinérance

La censure de la presse d'expression française du Québec durant la Première Guerre mondiale - Levert, Myriam (Université du Québec à Montréal, 2001)
Keywords: Guerre

L'apport des services de proximité en matière de revitalisation socio-économique des quartiers - Rochefort, Michel (Université du Québec à Montréal, 2001)
Keywords: Quartiers

Marginalité, espace public et citoyenneté: les enjeux de la gestion publique des espaces urbains - Charest, Guylaine (Université du Québec à Montréal, 2001)

Tibetans in Québec: Proﬁle of a Buddhist Community - Cormier, Louis (Université du Québec à Montréal, 2001)
Keywords: Tibétains

Étude patrimoniale de la maison des Hurtubise - Robichaud, Léon; Stewart, Alan (Ministère de la Culture et des Communications, Institut d'histoire de l'Amérique française et Remparts, 2001)
Keywords: Logement

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens